THE MOŕAVKA METEORITE FALL: 3. METEOROID INITIAL SIZE, HISTORY, STRUCTURE, AND COMPOSITION - Borovǐcka J.; Weber H.W.; Schultz L.; Jopek T.; Jakěs P.; Haloda J.; T́ycov́a P.; Randa Z.; Kucera J.; Brown P.G.; ReVelle D.O.; Kalenda P.; et al. (My University, 2003)
The properties and history of the parent meteoroid of the Morávka H5–6 ordinary chondrites have been studied by a combination of various methods. The pre-atmospheric mass of the meteoroid was computed from fireball radiation, infrasound, seismic signal, and the content of noble gases in the meteorites. All methods gave consistent results. The best estimate of the pre-atmospheric mass is 1500 ± 500 kg. The fireball integral bolometric luminous efficiency was 9%, and the acoustic efficiency was 0.14%. The meteoroid cosmic ray exposure age was determined to be (6.7 ± 1.0) × 106 yr. The meteorite shows a clear deficit of helium, both 3He and 4He. This deficit can be explained by solar heating. Numerical backward integration of the meteoroid orbit (determined in a previous paper from video records of the fireball) shows that the perihelion distance was probably lower than 0.5 AU and possibly as low as 0.1 AU 5 Ma ago. The collision which excavated Morávka probably occurred while the parent body was on a near-Earth orbit, as opposed to being confined entirely to the main asteroid belt. An overview of meteorite macroscopic properties, petrology, mineralogy, and chemical composition is given. The meteorites show all mineralogical features of H chondrites. The shock level is S2. Minor deviations from other H chondrites in abundances of trace elements La, Ce, Cs, and Rb were found. The ablation crust is enriched with siderophile elements.